Advanced glycation end products reduce the calcium transient in cardiomyocytes by increasing production of reactive oxygen species and nitric oxide. Issue 11 (26th September 2017) - Hegab, Zeinab; Mohamed, Tamer M.A.; Stafford, Nicholas; Mamas, Mamas; Cartwright, Elizabeth J.; Oceandy, Delvac
Abstract : Advanced glycation end products (AGE) are central to the development of cardiovascular complications associated with diabetes mellitus. AGE may alter cellular function through cross‐linking of cellular proteins or by activating the AGE receptor (RAGE). However, the signalling molecules involved during AGE stimulation in cardiomyocytes remain unclear. Here, we investigated the effects of AGE treatment on intracellular calcium homeostasis of isolated cardiomyocytes and studied the activation of signalling molecules involved in this process. Treatment of cardiomyocytes with AGE for 24 h resulted in a dose‐dependent reduction in calcium transient amplitude, reaching a maximum 50% reduction at a dose of 1 mg·mL −1 . This was accompanied with a 32% reduction in sarcoplasmic reticulum calcium content but without any detectable changes in the expression of major calcium channels. Mechanistically, we observed a significant increase in the production of reactive oxygen species (ROS) in AGE‐treated cardiomyocytes and enhancement of NADPH oxidase activity. This was accompanied with activation of p38 kinase and nuclear translocation of NF‐κB, and subsequently induction of inducible NO synthase (iNOS) expression, leading to excessive nitric oxide production. Overall, our data reveal the molecular signalling that may underlie the alteration of intracellular calcium homeostasis in cardiac myocytes due to AGE stimulation. This may provide new insights into the pathophysiological mechanisms of the development of diabetic cardiomyopathy. Abstract : Advanced glycation end products (AGE) are a leading cause of diabetic cardiomyopathy, yet the mechanisms behind their pathogenesis are unclear. We identified that AGE treatment in cardiomyocytes reduces the calcium transient and sarcoplasmic reticulum calcium content. This occurs due to S‐nitrosylation of calcium‐handling proteins following increased reactive oxygen species production through NADPH oxidase activation, and nitric oxide production via p38/NF‐κB/iNOS signalling.